COVID-19 DAN E-LEARNING: PERUBAHAN STRATEGI PEMBELAJARAN SAINS DAN LINGKUNGAN DI SMP - Ichsan, Ilmi Zajuli; Rahmayanti, Henita; Purwanto, Agung; Sigit, Diana Vivanti; Kurniawan, Edi; Dewi, Aryani Kadarwati; Wirdianti, Nina; Hermawati, Farah Muthi; Marhento, Giry (JINoP (Jurnal Inovasi Pembelajaran), 2020)
Corona Virus Diseases (Covid-19) has become an epidemic in Indonesia and even has become a global pandemic in 2020. Various impacts of Covid-19 is one of them changes learning strategy. One of them is the change from conventional learning to internet-based learning or electronic learning (e-learning). The purpose of this study was to describe the e-learning in natural science and environmental learning during the Covid-19 outbreak. The research method used descriptive method and data collection techniques using a survey through Google Form. The study was conducted during March 2020 in Bekasi city and Bandung city, when the Covid-19 outbreak began in Indonesia. The results of this study indicate that there are many limitations. Findings showed that Whatsapp was the highest e-learning media (65.54%). Related to the biggest obstacle is about internet quota in a cellular phone (27.03%). Then students think the video (35.14%) was the best type of file to be shared in e-learning. Then the majority of students (54.73%) thought that the most effective duration for e-learning was 2-3 hours. The results of this study indicate that e-learning was not yet perfect and needs to be improved. The conclusion of this study was e-learning needs to be improved and need innovation.